Small wind generation using complex airfoil turbine. Issue 1 (1st January 2019) - Lin, Chin E.; Phan, Bao Chau; Chuang, Jia-Shian
Abstract: Near-ground wind is not stable and turbulent due to the ground effect and heat ventilation. Small wind generation system design for public utilities needs to catch the small wind to rotate the turbine blades. Ground wind gust contains horizontal and vertical ventilation. A complex airfoil wind turbine is proposed in this paper for a special shape design to combine the horizontal and vertical blades which can deal with the different directions of the wind. Based on Bernoulli's Law, these wind turbine blades are designed and assembled in the same axis shaft. Using 3D printing and metal machining, a small experiment system is constructed to meet the system demand and integrated to verify the complex design. Simulations and experiments are presented to demonstrate the complex turbine in near-ground operation. This design fits for small power generation in public utility applications such as street lights and emergency power in a remote shelter cabin. Systematic design and fabrication are completed for preliminary tests. The proposed complex airfoil turbine enhances small wind system performance and improves 15 20% efficiency.